Preliminary clinical association between the Nerve-Sparing Quality (NSQ) Score and early functional outcomes after robot-assisted radical prostatectomy - Kempisty, Jakub; Balawender, Krzysztof; Dąbrowski, Oskar; Burdziak, Karol (Folia Medica Cracoviensia, 2026)
Introduction: Nerve-sparing during robot-assisted radical prostatectomy (RARP) plays a critical role in postoperative functional recovery, particularly urinary continence and erectile function. Although several tools exist for assessing surgical performance in robotic surgery, objective intraoperative evaluation of nerve-sparing quality remains limited. The Nerve-Sparing Quality (NSQ) Score was recently introduced as a structured intraoperative scoring system designed to evaluate the technical quality of neurovascular bundle preservation. The aim of the present study was to explore the preliminary clinical correlation between NSQ Score and early functional outcomes following RARP. Methods: This retrospective observational study included 20 patients who underwent RARP and had available intraoperative NSQ Score assessment together with 6-month postoperative functional follow-up. The NSQ Score is a 10-point intraoperative scoring system based on five domains: dissection plane, bleeding control, bundle manipulation, continuity of dissection, and symmetry. Functional outcomes were assessed at 6 months using data obtained from routine postoperative follow-up records, using pad use (pads per day) and the International Index of Erectile Function-5 (IIEF-5). Associations between NSQ Score and functional outcomes were evaluated using Spearman correlation analysis. Exploratory subgroup comparisons were performed using an NSQ Score threshold of ≥8. Results: The mean NSQ Score was 7.95 ± 1.61. Mean pad use at 6 months was 0.75 ± 0.91 pads/day, and mean IIEF-5 score was 18.05 ± 6.60. Higher NSQ Score correlated with lower pad use (Spearman ρ = −0.56, p = 0.011) and higher IIEF-5 (ρ = 0.87, p < 0.001). Patients with NSQ Score ≥8 demonstrated significantly better erectile function compared with those with lower scores (21.38 ± 4.46 vs 11.86 ± 5.40, p = 0.001) and lower pad use (0.38 ± 0.51 vs 1.43 ± 1.13 pads/day, p = 0.035). Conclusions: Higher NSQ Score was associated with improved early functional outcomes after RARP, particularly regarding erectile function and postoperative pad use. These findings provide preliminary clinical support for the construct validity of the NSQ Score as a structured intraoperative measure of nerve-sparing quality. Larger prospective studies incorporating baseline functional parameters are required to determine the independent predictive value of the NSQ Score.